2012
DOI: 10.1002/rcm.6127
|View full text |Cite
|
Sign up to set email alerts
|

Perfluorooctanoic acid and ammonium perfluorooctanoate: volatile surfactants for proteome analysis?

Abstract: APFO is considered a favoured alternative to SDS for proteome solubilization. Strictly speaking, APFO is not an 'MS-friendly' surfactant for proteome characterization; the detergent not only suppresses ESI signals at high concentration, but also perturbs reversed phase separation. However, the simplicity of APFO removal ahead of LC/MS justifies its use over the conventional SDS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…To address the poor MS compatibility of detergents like SDS, where an upper limit threshold for the presence of SDS in sample is only 0.01% , several new acid‐labile detergents have been commercialized within the past decade. These include sodium 3‐[(2‐methyl‐2‐undecyl‐1,3‐dioxolan‐4‐yl)methoxy]‐1‐propanesulfonate (RapiGest, Waters) and 3‐[3‐(1,1‐bisalkyloxyethyl)pyridin‐1‐yl]propane‐1‐sulfonate (PPS, Protein Discovery).…”
Section: Solubilization Of Mps and Ms Compatibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…To address the poor MS compatibility of detergents like SDS, where an upper limit threshold for the presence of SDS in sample is only 0.01% , several new acid‐labile detergents have been commercialized within the past decade. These include sodium 3‐[(2‐methyl‐2‐undecyl‐1,3‐dioxolan‐4‐yl)methoxy]‐1‐propanesulfonate (RapiGest, Waters) and 3‐[3‐(1,1‐bisalkyloxyethyl)pyridin‐1‐yl]propane‐1‐sulfonate (PPS, Protein Discovery).…”
Section: Solubilization Of Mps and Ms Compatibilitymentioning
confidence: 99%
“…However, the data indicated significant improvements in hydrophobic peptide recovery, especially for late‐eluting peptides, with even ten‐fold enhancements in intensity for some peptides reported. More recently, there has been interest in the use of fluorinated surfactants as alternatives to SDS, with ammonium perfluorooctanoate (2–4% w/v) found to have good solubilization ability, and easy removal by evaporation after acidification .…”
Section: Solubilization Of Mps and Ms Compatibilitymentioning
confidence: 99%
“…Surfactants are used in proteomic research to facilitate solubilization and digestion of proteins . We and others recently reported that a volatile surfactant, perfluorooctanoic acid (PFOA), solubilizes membrane proteins as effectively as sodium dodecyl sulfate (SDS) , the gold standard in protein solubilization. Unlike SDS, PFOA (up to 0.5%, w/v) does not inhibit trypsin activity, making the surfactant compatible with protein digestion by trypsin .…”
Section: Recoveries Of Bsa Peptides From Scx Hilic and Fspementioning
confidence: 99%
“…The evaporation of PFOA is achieved by repeatedly evaporating and reconstituting the protein digests from ethanol:ethylacetate:water:TFA (0.33:0.33:0.33:0.01, v/v/v/v) under both in vacuo and atmospheric pressure . The evaporation procedure is a lengthy process taking approximately 6 h. Although, Vieira and co‐workers have recently reported that PFOA can be evaporated from 50 mM HCl in 2 h , finding a more rapid alternative would increase the relevance of PFOA in proteomic research.…”
Section: Recoveries Of Bsa Peptides From Scx Hilic and Fspementioning
confidence: 99%
“…Isomeric ions are separated by IMS-MS while migrating through a buffer gas with a drift velocity that will depend on the charge, shape (collision cross-section, CCS) and polarity. 17 IMS has been mainly used to analyze compounds such as drugs, chemical warfare agents, explosives, environmental pollutants, dendrimeric and polymeric structures, as well as proteins and peptides, 18,19 providing invaluable information about their conformation in the native solution environment. 20 Traveling wave ion mobility (TWIM) has been introduced more recently as a new mode of ion propulsion for IMS experiments.…”
Section: Introductionmentioning
confidence: 99%